The Effect Of Salt Solution Concentration On The Germination And Growth Of Water Lettuce (Lactuca Sativa Var. Angustana) - Safinatun Najeh, Siti; Sarwo Danuji; Lila Maharani (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
Salinity is one of the main obstacles in plant cultivation, especially during the germination and early growth stages. High salt concentrations can cause osmotic stress and ionic toxicity, thereby hindering water absorption and disrupting the physiological processes of the plant. This study aims to examine the effects of various concentrations of salt solution (NaCl) on the germination and early growth processes of water lettuce (Lactuca sativa var. angustana) in a hydroponic system. Soil salinity is a major problem in agriculture that can cause osmotic stress and ionic toxicity in plants, especially at the early growth stages such as germination. This condition hinders water absorption by the seeds and disrupts the balance of essential ions that play a role in cellular activities, thereby reducing the efficiency of physiological processes crucial for the formation of uniform and healthy plants. The research was conducted using a Randomized Complete Block Design. Complete with five treatments of NaCl concentration (0, 25, 50, 75, and 100 mM), each repeated three times. Seeds were sown on cotton media and watered with the solution according to the treatment for 14 days. The observed parameters include germination percentage, plant height, leaf count, and wet weight. The results show that the increase in NaCl concentration is inversely proportional to all growth parameters, where the treatment without NaCl yielded the best results, while the 100 mM concentration provided the lowest values. Statistical analysis confirmed the significant effect of salt concentration on the reduction of seed viability and vegetative growth of watercress. In conclusion, high salinity negatively impacts the physiology and early development of watercress through osmotic stress and ion toxicity mechanisms. These findings are important for the development of plant cultivation techniques in high-salinity areas and support the development of varieties that are more resistant to environmental stress, particularly in intensive agricultural systems such as hydroponics.